The effect of intergenerational rearing on young children’s self-control: The intervention effect of sports games - Sun, Boqian; Quan, Haiying; Zhang, Ye (Frontiers in Psychology, 2022)
Objective: To investigate the effect of different rearing methods on children's self-control and verify the promoting effect sports games might have on children's self-control in intergenerational rearing. Methods: A total of 72 intergenerational rearing children and 66 non-intergenerational rearing children were included in Experiment 1, in which the delay-of-gratification task was used to examine the differences in the self-control among children with different rearing methods. In experiment 2, 70 intergenerational rearing children were included as subjects, and sports games were used to improve their self-control. Results: The results of experiment 1 showed that compared with non-intergenerational rearing children, the self-control ability of intergenerational rearing children was poor. In experiment 2, it was found that after the intervention with sports games, the self-control ability of the children in the intergenerational rearing group was effectively improved. Conclusion: Although the intergenerational rearing methods have a certain negative impact on the self-control ability in children, the sports game intervention can be used to effectively develop the self-control ability of the intergenerational rearing children.